2004
DOI: 10.1111/j.1365-277x.2004.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of two environmental nutrition programmes and an educational nutrition programme conducted at supermarkets and worksite cafeterias in the Netherlands

Abstract: Introduction  This article describes the process evaluation of two environmental programmes and an educational nutrition programme, implemented at supermarkets and worksite cafeterias. Studies conducted earlier, indicated that the programmes had no effect on consumers’ eating behaviour. Consequently, the more specific purpose of the present study was to identify explanations for the ineffectiveness of the programmes and to formulate recommendations for future programmes. Materials and methods  The environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…The study sample sizes range from 37 supermarket customers [50] to more than 200,000 beneficiaries of a large intervention [23]. Most studies were conducted in the U.S.A. Four were conducted in Canada [5154], one in the UK [55], one in Japan [56], one in France [57], one in South Africa [23], one in Norway [58], one in Australia [27] three in New Zealand [5961], four in the Netherlands [26, 6264] and one in the Republic of Marshal Islands [65]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study sample sizes range from 37 supermarket customers [50] to more than 200,000 beneficiaries of a large intervention [23]. Most studies were conducted in the U.S.A. Four were conducted in Canada [5154], one in the UK [55], one in Japan [56], one in France [57], one in South Africa [23], one in Norway [58], one in Australia [27] three in New Zealand [5961], four in the Netherlands [26, 6264] and one in the Republic of Marshal Islands [65]. …”
Section: Resultsmentioning
confidence: 99%
“…Apart from few studies [55, 59, 60, 62, 63, 74], store interventions have been found to be effective in one or more of their main outcomes. In some studies, overall energy intake did not significantly change [50], although positive and significant change in targeted food was achieved.…”
Section: Resultsmentioning
confidence: 99%
“…This emphasizes the importance of developing strategies to improve the nutritional content in all meal types, making the healthier choices both more appealing and accessible for customers with different food choice preferences. It is, however, well recognized that improving the nutritional quality of food served by food services can be challenging, and efforts to change the food selection and content may be met with resistance by both canteen staff and customers (33)(34)(35) . In order to support the ongoing progress towards healthier menu meals, the provision of an assessment tool directed at worksite canteens would be valuable for conducting self-evaluation and setting targets for work (36) .…”
Section: Discussionmentioning
confidence: 99%
“…Although a majority of consumers have a reasonable knowledge of nutrition and can use nutrition labels when prompted, only a minority seem to look at the nutrition labels when shopping (Black & Rayner, 1992;Grunert, 2008;Steenhuis, van Assema, Reubsaet, & Kok, 2004). It thus seems that (lack of) attention may be an important bottleneck in the context of nutrition information on the product packaging (Van Trijp, 2009).…”
Section: Introductionmentioning
confidence: 95%